Subcellular partitioning of protein tyrosine phosphatase 1B to the endoplasmic reticulum and mitochondria depends sensitively on the composition of its tail anchor - Füller, Julia; Grabenbauer, Markus (PLOS ONE, 2015)
The canonical protein tyrosine phosphatase PTP1B is an important regulator of diverse cellular signaling networks. PTP1B has long been thought to exert its influence solely from its perch on the endoplasmic reticulum (ER); however, an additional subpopulation of PTP1B has recently been detected in mitochondria extracted from rat brain tissue. Here, we show that PTP1B’s mitochondrial localization is general (observed across diverse mammalian cell lines) and sensitively dependent on the transmembrane domain length, C-terminal charge and hydropathy of its short (≤35 amino acid) tail anchor. Our electron microscopy of specific DAB precipitation revealed that PTP1B localizes via its tail anchor to the outer mitochondrial membrane (OMM), with fluorescence lifetime imaging microscopy establishing that this OMM pool contributes to the previously reported cytoplasmic interaction of PTP1B with endocytosed epidermal growth factor receptor. We additionally examined the mechanism of PTP1B’s insertion into the ER membrane through heterologous expression of PTP1B’s tail anchor in wild-type yeast and yeast mutants of major conserved ER insertion pathways: In none of these yeast strains was ER targeting significantly impeded, providing in vivo support for the hypothesis of spontaneous membrane insertion (as previously demonstrated in vitro). Further functional elucidation of the newly recognized mitochondrial pool of PTP1B will likely be important for understanding its complex roles in cellular responses to external stimuli, cell proliferation and diseased states.
Gesehen am 06.08.2021